Cooperative Learning Model with Jigsaw Type Improves Students’ Sciences Process Skills and Learning Outcomes - Soedimardjono, Fransiska Purwantini; P., Pratiwi (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2021)
This study aims to improve science process skills and learning outcomes with Classroom Action Research using a jigsaw-type cooperative learning model. This research is a classroom action research conducted in two cycles. Learning outcomes before the results of the study using a jigsaw cooperative model is 33%. The results showed that an increase in student learning outcomes in the initial research, cycle I, and cycle II. The average value, in the initial study the average value of the class test was 57.33 in the first cycle, the average grade was 82.66, and in the second cycle, the average grade was 86.66. In addition, the number of students who graduated also increased, in the initial study the number of students who graduated was only 10 people (33%), and 20 other people (67%) did not graduate. In the first cycle the number of students who graduated increased to 26 people (87%) students who did not pass 4 people (13%). An increase in the number of students who graduated was also seen in cycle II the number of students who passed 30 people (100%) or thus learning with the Jigsaw Cooperative model was more appropriate to be carried out so that all students graduated.